Acceptance of biomass plants – Results of a longitudinal study in the bioenergy-region Altmark. (November 2015) - Kortsch, Timo; Hildebrand, Jan; Schweizer-Ries, Petra
Abstract: The present contribution addresses the results of a longitudinal study in a 'bioenergy-region' concerning the public acceptance of biomass plants and the corresponding influencing factors. Using a standardized questionnaire, 423 persons were polled between 2009 and 2011 on three points of measurement in four places in the bioenergy-region Altmark. One main result of the study is that the reported public acceptance remains constantly high over time; nevertheless it became evident that the respective influencing factors differ in their strength, whereas the perceived regional benefit shows a strong connection to the reported public acceptance of biomass plants at each point of measurement. Concluding the research results, the acceptance of biomass plants doesn't seem to be a fixed construct, but has to be seen in context of the respective experiences with plants on a local level over time. In addition to the local population, key actors of the regional biomass sector were also interviewed (N = 26). The analyses show significant differences in the perception and evaluation of the current informational level between the population and the key actors. Furthermore, the key actors estimated the utilisation of biomass even more positively and expected a greater 'signal function' of the bioenergy-region-project compared to the population. Highlights: Development of public acceptance of biomass plants is studied over three years. The reported public acceptance remains constantly high over time. The perceived regional benefit shows a strong connection to the acceptance. Additionally, key actors of the regional biomass sector were interviewed. There are significant differences in actors' to the populations' perception.